2023
DOI: 10.1101/2023.01.04.23284200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of early life experiences and gut microbiota on neurobehavioral development among preterm infants: A longitudinal cohort study

Abstract: Objectives: To investigate the impact of early life experiences and gut microbiota on neurobehavioral development among preterm infants during neonatal intensive care unit (NICU) hospitalization. Methods: Preterm infants were followed from the NICU admission until their 28th postnatal day or until discharge. Daily stool samples, painful/stressful experiences, feeding patterns, and other clinical and demographic data were collected. Gut microbiota was profiled using 16S rRNA sequencing, and operational taxonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Veillonella, Clostridium sensu stricto, Ruminococcus, Intestinibacter, and Blautia as well as an unspecified genus from the Lachnospiraceae family. Some of the taxa we identified, such as Veillonella and Clostridium sensu stricto, have been previously identified in studies of infant and child gut microbiota and brain and behavioral development (Acuña et al, 2021;Chen et al, 2023;Flannery et al, 2020), although the directionality of associations between taxa and child outcomes has differed between studies. Warner and colleagues (2023) identified a few species of bacteria from Veillonella that were differentially abundant in infants as a function of prenatal caregiver social wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Veillonella, Clostridium sensu stricto, Ruminococcus, Intestinibacter, and Blautia as well as an unspecified genus from the Lachnospiraceae family. Some of the taxa we identified, such as Veillonella and Clostridium sensu stricto, have been previously identified in studies of infant and child gut microbiota and brain and behavioral development (Acuña et al, 2021;Chen et al, 2023;Flannery et al, 2020), although the directionality of associations between taxa and child outcomes has differed between studies. Warner and colleagues (2023) identified a few species of bacteria from Veillonella that were differentially abundant in infants as a function of prenatal caregiver social wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the gut microbiota of preterm infants is associated with early cognitive and behavioral neurodevelopment (Chen et al, 2023; Sarkar et al, 2022) and has been identified as a potential biomarker of neurodevelopmental delay in preterm infants (Roze et al, 2020). Disruption of the maturation and development of the microbiome has also been linked to a number of fatal diseases in preterm infants, including NEC and late‐onset sepsis (Masi & Stewart, 2019; Thanert et al, 2021).…”
Section: Glial Cells and Mechanismsmentioning
confidence: 99%